Brand Coolness. (September 2019) - Warren, Caleb; Batra, Rajeev; Loureiro, Sandra Maria Correia; Bagozzi, Richard P.
Marketers strive to create cool brands, but the literature does not offer a blueprint for what "brand coolness" means or what features characterize cool brands. This research uses a mixed-methods approach to conceptualize brand coolness and identify a set of characteristics typically associated with cool brands. Focus groups, depth interviews, and an essay study indicate that cool brands are perceived to be extraordinary, aesthetically appealing, energetic, high status, rebellious, original, authentic, subcultural, iconic, and popular. In nine quantitative studies (surveys and experiments), the authors develop scale items to reliably measure the component characteristics of brand coolness; show that brand coolness influences important outcome variables, including consumers' attitudes toward, satisfaction with, intentions to talk about, and willingness to pay for the brand; and demonstrate how cool brands change over time. At first, most brands become cool to a small niche, at which point they are perceived to be more subcultural, rebellious, authentic, and original. Over time, some cool brands become adopted by the masses, at which point they are perceived to be more popular and iconic.